Relation between left ventricular gradient and relative stroke volume ejected in early and late systole in hypertrophic cardiomyopathy. Assessment with radionuclide cineangiography. Issue 6 (December 1984) - Sugrue, D D; McKenna, W J; Dickie, S; Myers, M J; Lavender, J P; Oakley, C M; Goodwin, J F
Abstract : Hypertrophic cardiomyopathy is characterised by hyperkinetic left ventricular function, but the effect of an outflow tract gradient on the haemodynamics of ejection remains controversial. To determine the functional importance of left ventricular gradients in hypertrophic cardiomyopathy technetium-99m gated equilibrium radionuclide angiography was performed in 18 normal subjects and 57 patients, 26 with and 31 without left ventricular gradients. Time activity curves were generated from list mode data, and the proportion of stroke volume ejected during various phases of systole was computed. The proportion of stroke volume ejected during the initial third, the initial 50%, and the initial 80% of systole was greater in patients with hypertrophic cardiomyopathy than in normal subjects but was identical in patients with and without left ventricular gradients. The duration of systole was similar in the three groups. These findings favour the interpretation that a left ventricular gradient does not represent true obstruction and are consistent with previous observations that clinical features and prognostic indicators do not relate to gradients in this disease.